Auctions : theory and practice - Klemperer, Paul (Toulouse lectures in economics., 2004)
"Governments use them to sell everything from oilfields to pollution permits, and to privatize companies; consumers rely on them to buy baseball tickets and hotel rooms, and economic theorists employ them to explain booms and busts. Auctions make up many of the world's most important markets; and this book describes how auction theory has also become an invaluable tool for understanding economics.